Study on the Evolution of Research in the Field of Accounting Regulation Related to Insurance Contracts - Cristina Gabriela COSMULESE; Adriana REUȚ (BURSUC); Marius-Sorin Ciubotariu; Rozalia KICSI; Mărioara MOLOCINIUC (HRIȚCAN) (Communications of International Proceedings, 2021)
The aim of this paper is to conduct a bibliometric analysis by which the key concepts of this research, i.e. insurance contract, IFRS 4 and IFRS 17, are studied. The research methodology consisted in the fact that three distinct bibliometric analyses were developed for these terms, which refer to the following aspects: which geographical regions have published articles on the analyzed topics, the citation index related to these concepts, and a more detailed analysis using clusters of the mentioned concepts. The results of the research reveal that this sector of the economy is booming, especially in the current context of the COVID-19 pandemic, in the sense that the population is trying to insure itself against this new virus, especially when travelling. The analysis has shown that the insurance sector will increase its number of publications in the coming years as the pandemic has taken its toll.
Keywords: Insurance contract; IFRS 4; IFRS 17; bibliometric analysis; COVID-19